Developments in spiritual care education in German - speaking countries - Paal, Piret (BioMed Central, 2014)
BACKGROUND: This article examines spiritual care training provided to healthcare professionals in Germany, Austria and Switzerland. The paper reveals the current extent of available training while defining the target group(s) and teaching aims. In addition to those, we will provide an analysis of delivered competencies, applied teaching and performance assessment methods. METHODS: In 2013, an anonymous online survey was conducted among the members of the International Society for Health and Spiritual Care. The survey consisted of 10 questions and an open field for best practice advice. SPSS21 was used for statistical data analysis and the MAXQDA2007 for thematic content analysis. RESULTS: 33 participants participated in the survey. The main providers of spiritual care training are hospitals (36%, n = 18). 57% (n = 17) of spiritual care training forms part of palliative care education. 43% (n = 13) of spiritual care education is primarily bound to the Christian tradition. 36% (n = 11) of provided trainings have no direct association with any religious conviction. 64% (n = 19) of respondents admitted that they do not use any specific definition for spiritual care. 22% (n = 14) of available spiritual care education leads to some academic degree. 30% (n = 19) of training form part of an education programme leading to a formal qualification. Content analysis revealed that spiritual training for medical students, physicians in paediatrics, and chaplains take place only in the context of palliative care education. Courses provided for multidisciplinary team education may be part of palliative care training. Other themes, such as deep listening, compassionate presence, bedside spirituality or biographical work on the basis of logo-therapy, are discussed within the framework of spiritual care. CONCLUSIONS: Spiritual care is often approached as an integral part of grief management, communication/interaction training, palliative care, (medical) ethics, psychological or religious counselling or cultural competencies. Respondents point out the importance of competency based spiritual care education, practical training and maintaining the link between spiritual care education and clinical practice. Further elaboration on the specifics of spiritual care core competencies, teaching and performance assessment methods is needed.